From traditional to transitional texts: Montenegrin oral tradition and Vuk Karadžić’s Narodne srpske pjesme - Pavlovic, Aleksandar (2012)
This thesis analyses the influence of literate culture on the corpus of Montenegrin oral epic songs published in Vuk Karadžić’s edition of Narodne srpske pjesme from 1823 to 1833. The Introduction places the research in the scholarly context of the Parry-Lord theory of oral composition, later analyses of transitional texts that contain both oral traditional and literary characteristics, and recent interest in the entire process of transcription, edition and publication of songs belonging to the oral tradition. This is followed by an outline of facts relevant to the social and political history of Montenegro, its epic tradition and earliest textual representation. The first chapter discusses in detail the concepts of oral traditional, transitional and nontraditional texts and offers a synthetic theoretical framework for the analysis of transitional South Slavonic oral songs, based on their phraseology, style, outlook and contextual evidences about their documentation and singers. In the second chapter, this is followed by a textual analysis of five genuine oral traditional Montenegrin songs from Karadžić’s collection and a discussion of their style, themes and overall perspective. In the third chapter, two songs about contemporary Montenegrin battles from the collection are analysed and identified as proper transitional texts; they contain a number of literary elements and were influenced by the Montenegrin ruler Bishop Petar I, but also retain to some extent the characteristics of traditional oral songs. The final chapter identifies nontraditional elements in the four songs that Karadžić wrote down from a literate Montenegrin singer Đuro Milutinović Crnogorac. It is argued that these songs combine a traditional style and outlook with elements distinct from local oral tradition, which the singer had adopted during his education and under the influence of Bishop Petar. The main conclusion of the thesis is that the earliest publication of Montenegrin oral tradition already contained a number of features of literary origin; two out of eleven songs are proper transitional texts, and four others display the influence of literate culture. These texts and features did not originate in the local oral tradition; rather, they were introduced by a literate singer close to the political leadership and then incorporated in the collection of oral traditional songs during the process of its literary documentation and representation. By revealing the complex socio-political framework giving rise to the early-nineteenth century collections of South Slavonic oral songs, this thesis makes a contribution to current research in the textualisation of the oral tradition, and provides a consistent model for the analysis of transitional texts in oral studies.